Tumor-Infiltrating Lymphocytes in Colorectal Cancer: The Fundamental Indication and Application on Immunotherapy - Bai, Ziyi; Zhou, Yao; Ye, Zifan; Xiong, Jialong; Lan, Hongying; Wang, Feng (Frontiers in Immunology, 2022)
The clinical success of immunotherapy has revolutionized the treatment of cancer patients, bringing renewed attention to tumor-infiltrating lymphocytes (TILs) of various cancer types. Immune checkpoint blockade is effective in patients with mismatched repair defects and high microsatellite instability (dMMR-MSI-H) in metastatic colorectal cancer (CRC), leading the FDA to accelerate the approval of two programmed cell death 1 (PD-1) blocking antibodies, pembrolizumab and nivolumab, for treatment of dMMR-MSI-H cancers. In contrast, patients with proficient mismatch repair and low levels of microsatellite stability or microsatellite instability (pMMR-MSI-L/MSS) typically have low tumor-infiltrating lymphocytes and have shown unsatisfied responses to the immune checkpoint inhibitor. Different TILs environments reflect different responses to immunotherapy, highlighting the complexity of the underlying tumor-immune interaction. Profiling of TILs fundamental Indication would shed light on the mechanisms of cancer-immune evasion, thus providing opportunities for the development of novel therapeutic strategies. In this review, we summarize phenotypic diversities of TILs and their connections with prognosis in CRC and provide insights into the subsets-specific nature of TILs with different MSI status. We also discuss current clinical immunotherapy approaches based on TILs as well as promising directions for future expansion, and highlight existing clinical data supporting its use.